2013
DOI: 10.1016/j.bcp.2013.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Gimatecan and other camptothecin derivatives poison Leishmania DNA-topoisomerase IB leading to a strong leishmanicidal effect

Abstract: The aim of this work is the in vitro and ex vivo assessment of the leishmanicidal activity of camptothecin and three analogues used in cancer therapy: topotecan (Hycantim®), gimatecan (ST1481) and the pro-drug irinotecan (Camptosar®) as well as its active metabolite SN-38 against Leishmania infantum. The activity of camptothecin and its derivatives was studied on extracellular L. infantum infrared-emitting promastigotes and on an ex vivo murine model of infected splenocytes with L. infantum fluorescent amastig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…In free DOX treated cells, nuclei showed a 15‐fold higher fluorescence level than PG‐DOX(pH)‐PEG treated cells, confirming that our nanoparticle avoids drug deposition in the nuclei. The accumulation of free DOX in nucleus or mitochondria is a major drawback of this drug as well as of other drugs, such as the topoisomerase‐I poisoning derivatives (camptothecin derivatives and indenoisoquinolines) that have shown to be active against intracellular‐leishmania amastigotes but are highly toxic to host cells …”
Section: Resultsmentioning
confidence: 99%
“…In free DOX treated cells, nuclei showed a 15‐fold higher fluorescence level than PG‐DOX(pH)‐PEG treated cells, confirming that our nanoparticle avoids drug deposition in the nuclei. The accumulation of free DOX in nucleus or mitochondria is a major drawback of this drug as well as of other drugs, such as the topoisomerase‐I poisoning derivatives (camptothecin derivatives and indenoisoquinolines) that have shown to be active against intracellular‐leishmania amastigotes but are highly toxic to host cells …”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors of respiratory chain complexes were able to induce apoptotic cell death on the blood stream form of L. donovani [13]. Topoisomerase I poison camptothecin, promotes protein-DNA cleavable complex formation leading to apoptosis-like cell death in Leishmania donovani [14], [15]. Miltefosine, the latest antileishmanial drug introduced in the market and the first effective oral treatment of VL, was initially developed as an anticancer drug [16] and induce apoptosis-like cell death in Leishmania donovani [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that inhibition of DNA topoisomerases should affect mainly cell cycling cells such cancer cells (22, 5659), but the toxicity assays performed here against the LM3 cells demonstrated that CP2 presents low selectivity for these cancer cells compared to Leishmania amastigotes, which could be indicative of the selectivity to the parasite's molecular target. It is worth noting that structural differences between human DNA topoisomerase I and Ld Topo1B might be the reason of the higher selectivity of CP2 to the parasite over the LM3 cells.…”
Section: Discussionmentioning
confidence: 64%